Heavy Metal Pollution and Sources in Dust from Primary Schools and Kindergartens in Ramadi City, Iraq - Radhi, Athraa B.; Shartooh, Sufyan M.; Al-Heety, Emad A. (Iraqi Journal of Science, 2021)
The aim of this study is to determine the level of pollution with heavy metals (Cd, Cr, Cu, Ni, Pb, Zn) and their potential sources in dust samples collected from schools in Ramadi City, Iraq. The dust samples were collected from 40 primary schools and two kindergartens and analyzed by using atomic absorption spectrophotometer. The heavy metal concentrations were found to follow the order Cr > Cu > Pb > Ni > Zn > Cd. The results indicated that the concentrations of Cd, Cu, and Pb exceeded the permitted background values. The pollution level was assessed using the geo-accumulation index (Igeo) and pollution load index (PLI). The classification of dust samples according to Igeo values showed that they ranged from unpolluted for Cu, Cr, Ni, and Zn, to moderately polluted for Pb, and heavily polluted for Cd. The PLI values indicated no to moderate pollution load. The results of the comparisons of heavy metal concentrations with the background values, as well as the multivariate statistical analysis, indicated three groups of heavy metals with different sources or origins: (1) Cd and Cu (anthropogenic source: vehicle emissions); (2) Pb (mixed source); and (3) Cr, Ni, and Zn (Geogenic source). This study is the first attempt in Iraq to investigate the concentrations of heavy metals in the dust of indoor environments. This study provides the environmental protection managers and decision-makers with important information about the concentrations of heavy metals and their sources in indoor environments.